Deciphering chiral structures in soft materials via resonant soft and tender X-ray scattering. (June 2020) - Cao, Yu; Feng, Chenrun; Jakli, Antal; Zhu, Chenhui; Liu, Feng
The highlights of this review include: Theoretical consideration of resonant scattering from form factor to signal intensity calculation is introduced. The practical experimental environment and sample preparation procedure are briefly introduced to show the current experimental capacity and limitation of resonant scattering. Studies on 1D/3D chiral structures, via soft and tender resonant X-ray scattering, are thoroughly reviewed. The helical pitch recognition and the structural elucidation ability of resonant scattering are properly summarized and explained. The potential applications and future improvements of resonant scattering are clearly stated in perspective of both researcher and facility developer. Abstract: Chirality is an essential research topic in material science, especially in soft materials including liquid crystals, polymers and biomaterials. There have been many discussions about chiral structures since people discovered and studied this particular property. Yet, due to the lack of effective characterization methods, many questions on helical structures of chiral materials remain unsolved. Here, we review recent applications of resonant soft (RSoXS) and tender resonant X-ray scattering (TReXS) on chirality study in soft materials, with a focus on liquid crystals phases. In the end, a perspective is presented on the potential applications and future improvements of resonant scattering. Graphical abstract: Image, graphical abstract